ARCIC III in the light of ARCIC II A critical response to Life in Christ, Morals, Communion and the Church - Baker, Frances (2017)
The Mandate of ARCIC II was to examine the differences which separate the Anglican and Roman Catholic communions. In the development of the Statement Life in Christ: Morals, Communion and the Church, this Mandate worked against the possibility of an outcome which would lead to a shared understanding of Christian moral life. The major focus of the Statement, the two issues on which there were formal statements of disagreement between the two communions, led to a very narrow focus for Christian life in the light of the gospel and a sense that the differences were too great to allow for resolution. Further exploration of the implications of our shared baptismal call in Christ and its implication for Christian living could have provided a much stronger basis for the consideration of particular moral issues and ethical reasoning that is an expression of "Life in Christ". The process of ARCIC III may facilitate a broader understanding of Christian moral life and a more nuanced articulation of ethical reasoning and moral culpability within the Roman Catholic moral tradition. These in turn may provide a more hopeful path towards communion with regard to the discernment of right ethical teaching.
Keywords: ARCIC II; ARCIC III; Discipleship; Life In Christ; Moral Life; Rezension